The construction of lay education in Argentina, Brazil, and Mexico (1824-1879) - Ortiz Cirilo, Alejandro (Centro de Estudios Avanzados, 2019)
This paper reconstructs the processes of conformation of the educational laicity regimes of Argentina, Brazil and Mexico, emphasizing the different stages present in the construction of their educational systems. The specificities of public and private schools, at different educational levels and in different historical contexts, are taken up again, focusing on the legal aspects that served as norms.